Ameliorative effects of Chlorophytum borivilianum on atopic dermatitis via modulation of inflammatory biomarkers and GC–MS-based metabolite profiling - Beenish Razzaq; Sana Jameel; Ayesha Asif; Zaib Ali Shaheryar; Muhammad Shafeeq ur Rehman; Ayman M. Al-Qaaneh (Molecular Biology Reports, 2026)

Experimental evaluation of porosity-induced performance enhancement in intermittent microwave drying of carrot slices - Muhammad Usama; Zaib Ali; Macmanus C. Ndukwu; Waseem Mushtaq; Aashir Iqbal; Tahmid Hassan Rupam (Food and Bioproducts Processing, 2026)

Retraction notice to “Polyvinyl alcohol and aminated cellulose nanocrystal membranes with improved interfacial compatibility for environmental applications” [Environ. Res. 214 (2022) 113793] - Saleem Ahmad; Zaib Jahan; Farooq Sher; Muhammad Bilal Khan Niazi; Tayyaba Noor; Honghao Hou; Ofaira Azhar; Emina Karahmet Sher (Environmental Research, 2026)

The Methodological Evolution of the Water-Food-Energy Nexus Index in Agriculture: A Systematic Review - Nisar Muhammad; Rashid Farooq; Khan Zaib Jadoon; Ghufran Ahmed Pasha (Water Resources Management, 2026)
The Water-Food-Energy (WFE) nexus has become a central framework for addressing resource sustainability in agriculture, yet its operationalization increasingly relies on composite indices whose methodological foundations remain fragmented. This study presents the first systematic and critical review of the Water-Food-Energy Nexus Index (WFENI) applied in agricultural systems. Following a rigorous PRISMA-guided protocol, we analyzed 21 peer-reviewed studies to examine indicator selection, index construction, weighting schemes, and validation practices. The review reveals a clear methodological evolution from early resource-efficiency metrics toward expanded frameworks that integrate environmental, climate, and emission dimensions. While normalization approaches are largely standardized, substantial divergence exists in weighting and aggregation, marking a gradual shift from equal and expert-based weights toward data-driven and optimization-based methods. However, a critical “robustness gap” persists: the vast majority of studies lack formal sensitivity or uncertainty analysis, raising serious concerns about reliability. This review systematically maps these methodological trends and outlines a strategic agenda for future research, advocating for the institutionalization of robustness testing, dynamic modeling, and expanded system boundaries to enhance the rigor and policy relevance of agricultural sustainability assessments.

Slow-Release DAP Fertilizer Coated with Bacillus velezensis FB2 and Polyvinyl Alcohol for Sustainable Maize Production - Zumrah Rehman; Muhammad Bilal Khan Niazi; Zaib Jahan; Ghulam Abbas Shah; Hazrat Ali; Zia Ur Rahman Farooqi; Waqas Mohy-Ud-Din; Qasim Ali; Gamal Awad El-Shaboury; Haitham Ibrahim El-Mekkawy (Journal of Soil Science and Plant Nutrition, 2026)

Controlling surface temperature in Intermittent Microwave Drying of potato slices using evaporative cooling: An experimental study - Muhammad Usama; Zaib Ali; Aashir Iqbal; Macmanus C. Ndukwu (Innovative Food Science & Emerging Technologies, 2026)

Is Critical Period for Weed Control Influenced by the Application of Pre-emergence Herbicide in Lentil (Lens culinaris Medik.)? - Muhammad Zia Ul Haq; Anas Ali; Gul Zaib Hassan; Rana Nadeem Abbas; Saira Shafiq; Mubashar Nadeem (International Journal of Plant Production, 2026)

Decadal air quality dynamics in the Yangtze River Delta: Evidence from machine learning–driven analysis - Shah Zaib; Muhammad Zeeshaan Shahid; Imran Shahid (Air Quality, Atmosphere & Health, 2026)

Emerging contaminants and their influence on plants: An in-depth review - Sadia Aziz; Sania Zaib; Azhar Iqbal; Muhammad Asif Chuadhry; Shaheen Shahzad; Bikram Dhara; Athanasios Alexiou; Partha Biswas; Mohamed M. Abdel-Daim; Shabana Bibi (Environmental Toxicology and Pharmacology, 2026)

Electrochemical investigation of bimetallic oxide-carbon composite electrode: Towards enhanced supercapacitor applications - Zaib Ullah Khan; Muhammad Atif (Next Research, 2025)

A novel hybrid MOF–metal oxide electrochemical sensor for ultra-trace detection of cadmium ions - Sabah Haider; Mujahid Mustaqeem; Maria Zaib; Mohammed Ashraf Gondal; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa (Journal of Environmental Chemical Engineering, 2025)

High accuracy computational approach to study Casson hybrid nanofluid flow under induced magnetic field inside wavy walls configuration having peristaltic motion with entropy generation - Noreen Sher Akbar; Javaria Akram; S. Ijaz; Zaib Jahan; Taseer Muhammad; Muhammad Bilal Habib; M. Fiaz Hussain; M. Farooq (Dynamics of Atmospheres and Oceans, 2025)

Nanostructured Bimetallic Oxide/Graphene Nanocomposites for Next-Generation High-Performance Energy Storage - Zaib Ullah Khan; Jinghua Jiang; Muhammad Atif (International Journal of Environmental Research, 2025)

Effect of Ocimum tenuiflorum L. compounds on Oreochromis mossambicus: a combination of molecular docking, biochemical dynamics, and antifertility assessment - Sajida Afzal; Siraj Khan; Muhammad Nauman Khan; Zahida Nasreen; Hansa Gul; Mian Inam Zaib; Hameed Alsamadany; Khalid H. Alamer; Ibtisam M. Alsudays; Muhammad Tahir Naseem (Aquaculture International, 2025)

Characterization of ambient air quality and its relationship with respiratory morbidity in typical cities of Northwest China (NWC) - Shah Zaib; Jianjiang Lu; Gao Yan; Xiaowen Yin; Xiaoning Lei; Muhammad Zeeshaan Shahid; Azhar Siddique; Mariam A. Yousaf Al-Nesf (Air Quality, Atmosphere & Health, 2025)

Tuning water transport channels in sulfonated copolymer membranes for highly effective removal of arsenic and selenium from industrial wastewater - Syed Qamber Ali Zaidi; Muhammad Hafi Wadgama; Zaib Jahan; Muhammad Bilal Khan Niazi; Faheem Hassan Akhtar (Desalination, 2025)

Analyzing temporal changes in urban land use and climate dynamics through Google Earth Engine - Muhammad Zaib Arshad; Sajjad Hussain; Zafar Iqbal; Saeed Ahmad Qaisrani; Muhammad Mubeen; Muhammad Tahir; Shankar Karuppannan (Journal of Earth System Science, 2025)

Evaluating the effect of land use land cover changes on soil moisture index and vegetation indices using multi-spectral satellite data - Muhammad Zaib Arshad; Zafar Iqbal; Muhammad Saeed; Muhammad Saleem; Rizwan Mansha; M Abdullah-Al-Wadud; Aqil Tariq (Journal of Earth System Science, 2025)

Patho-physiological effects of environmental relevant concentrations of lufenuron in male Japanese quails - Silwat Saeed; Gulnaz Afzal; Hafiz Muhammad Ali; Riaz Hussain; Raheela Jabeen; Shumaila Kiran; Rehana Iqbal; Sana Alam; Amna Jalal; Zaib un Nisa; Dalia Fouad; Farid Shokry Ataya; et al. (Environmental Research, 2025)

Characteristics of aerosols and planetary boundary layer dynamics during biomass burning season - Muhammad Zeeshaan Shahid; Muhammad Imran Shahzad; Sundas Jaweria; Sadaf Javed; Shah Zaib; Imran Shahid (Natural Hazards, 2025)
The northeastern region of Pakistan (NEP) has experienced increased haze episodes over the past decade, primarily due to enhanced biomass burning activities during the post-monsoon season. Economic growth, urbanization and industrial development also controbuted to high pollutants levels that leads to decline in air quality and visibility. These elevated pollution levels over NEP (69–75.5°E, 27.4–34°N) are influenced by both meteorological conditions and anthropogenic activities. This study investigates aerosol concentrations before, during, and after the haze episode during November 2021 using model simulations and remote sensing data. The Modern-Era Retrospective Analysis for Research and Applications, version 2 (MERRA-2), along with satellite observations from the Moderate Resolution Imaging Spectroradiometer (MODIS), are used for validation and analysis of this haze episode. The results illustrate the key contributors to this haze event and showed the there is significant increases in aerosol components such as sulfate, black carbon, organic carbon, dust and aerosol optical depth (AOD). The planetary boundary layer (PBL) height, measured with Ceilometer LIDAR, showed decreasing trend in height from October to December that support aerosol accumulation near the surface during the the month of November. This month is also biomass burning, crop residue burning, season in the region. These haze episodes also impacts the atmospheric visibility that dropped below 2 km in November. These findings provide key insights into the complex interactions between meteorology, emissions, and haze formation in NEP region, and will provide policy makers to design effective mittigation strategies.

Developing an ocean governance regime for China-Pakistan economic corridor: a comparison of the marine environmental legislation and policy framework by utilizing CRILL methodology - Shijun Zhang; Qian Wu; M Jahanzeb Butt; Minerva Batool; Muhammad Murad Zaib Butt (Frontiers in Marine Science, 2025)
Bilateralism in ocean governance is a novel concept that can be developed under the existing International Environmental Law (IEL) and United Nations Convention on the Law of the Sea (UNCLOS). This research paper suggested that bilateralism in ocean governance is one of the Agenda of Sustainable Development Goal 14 (SDG 14). This research paper utilized the methodology of a Comprehensive Review of Law and Relevant Literature (CRILL methodology) and developed a theoretical and legal framework for bilateral ocean governance with the elements of capacity building, adaptation, precautionary approach and participation. Under the given elements of CRILL methodology, this paper analyzed and compared the ocean governance mechanisms of China and Pakistan and proposed that under the China-Pakistan Economic Corridor (CPEC) of the Belt and Road Initiative (BRI), these two States can develop a bilateral framework of ocean governance for the protection of the marine environment, preservation of fisheries and mitigation of ocean acidification and sea level rise. The results of the CRILL methodology are presented in the form of a proposal that institutional coordination is essential for the effectiveness of bilateral ocean governance cooperation, which is China’s regional agenda of BRI. Through such development, the two States, China and Pakistan, can share the mutual economic benefits of ocean development and can have a strong voice in the global ocean agenda.

Maize cultivar mixtures: a sustainable approach for weed management under reduced herbicide dose - Amina Shahbaz; Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Amar Matloob; Rizwan Maqbool; Muhammad Tayyab Hanif; Muhammad Abu Bakar Hayat (Phytoparasitica, 2025)

Utilization of locally sourced waste fats for biodiesel production: Experimental characterization and environmental life cycle assessment - Muhammad Aqil Khan; Nadeem Ahmed Sheikh; Khan Zaib Jadoon; Abubakr Ayub; Tabbi Wilberforce Awotwe; Rasikh Tariq (Biomass and Bioenergy, 2025)

Analysing Pakistan’s fisheries legislation and institutional framework: integrating Sustainable Development Goal 14 within the scope of International Fisheries Law - Liu Lina; Muhammad Murad Zaib Butt (Frontiers in Marine Science, 2025)
International Fisheries Law (IFL) provides innovative approaches to fisheries governance at national levels. The emergence of Sustainable Development Goal 14 (SDG 14) is phenomenal for fisheries because it creates new means for implementing IFL. Under SDG 14, fisheries governance for sustainable fisheries has become a complex and challenging task for any state. Developing States like Pakistan are struggling to achieve SDG 14 with new approaches to fisheries governance. The current situation of fisheries governance in Pakistan motivated the content of this research paper. This research paper adopted the comprehensive literature review (CLR) methodology to analyse existing fisheries governance mechanisms in Pakistan. Besides CLR, the paper also analysed a ‘case study’ on fisheries governance of Pakistan entitled ‘National Policy and Strategy for Marine Fisheries. Furthermore, one hundred sixty-seven research articles and national and international legislation on fisheries governance from 2010 - 2023 are analysed. The results of the CLR methodology suggested that an extensive integrated mechanism under a comprehensive framework should be developed for fisheries governance. The framework forwarded a policy mechanism incorporating sustainable development goals with SDG 14 that should be implemented coherently for sustainable fisheries. The discussion followed the analysis and suggested that regional to local and bottom-up and top-down approaches in fisheries governance are required to address the challenges to sustainable fisheries in Pakistan. The conclusion of the discussion portrayed that future research related to fisheries governance in Pakistan shall be based on the practical implementation of SDG 14.

Climate bond issuance and enterprise EESM competitiveness: Steps toward environmental and climate-responsible development - Munazza Naz; Zaib Maroof; Rehana Naheed; Muhammad Jawad (Journal of Cleaner Production, 2025)

Integrated Weed Management in Sunflower Using a Hybrid Mixture and Reduced Herbicide Dose - Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Muhammad Shahid Ibni Zamir; Amina Shahbaz; Muhammad Saqib (Journal of Crop Health, 2025)

Synergistic electrochemical performance of textile sludge based activated carbon with reduced graphene oxide as electrode for supercapacitor application - Naveed Ahmed Khan; Zaib Jahan; Naseem Iqbal; Muhammad Bilal Niazi; Rimsha Mehek (Waste Management, 2025)

Biochar-based adsorption for heavy metal removal in water: a sustainable and cost-effective approach - Jalal Bayar; Nawab Ali; Younsuk Dong; Uzair Ahmad; Muhammad Mehran Anjum; Gul Roz Khan; Muhammad Zaib; Arshad Jalal; Rovaid Ali; Liaqat Ali (Environmental Geochemistry and Health, 2024)

Anti-inflammatory and analgesic properties of Polyphyllin VI revealed by network pharmacology and RNA sequencing - Zhenglang Zhang; Tingting Wang; Zhenhui Luo; Muhammad Haris Zaib; Mengqin Yi; Hekun Zeng; Peiyang Li; Dan Tang; Alexei Verkhratsky; Hong Nie (Purinergic Signalling, 2024)

Development of a robust method for Cd(II) ions analysis using CeO2- and CeO2-Cu-BTC-based electrochemical sensors - Sabah Haider; Maria Zaib; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa; Shabnam Shahida; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

Supplementation of nano-biochar improved growth and physiological attributes in wheat seedlings exposed to salt stress through enhanced activity of hydrolysing and nitrogen metabolic enzymes and regulation of crucial metabolites - Waqas Yousaf; Anis Ali Shah; Muhammad Bilal Afzal; Zaib-un Nisa; Naila Ali; Muhammad Yasin Ashraf; Hosam O. Elansary; Aqeel Ahmad (South African Journal of Botany, 2024)

The impacts of microplastics and biofilms mediated interactions on sedimentary nitrogen cycling: A comprehensive review - Muhammad Salam; Hong Li; Fayuan Wang; Aneeqa Zaib; Wentao Yang; Qiaoqiao Li (Process Safety and Environmental Protection, 2024)

Zinc-Coated Urea with Gelatin-Enhanced Zinc Biofortification, Apparent Nitrogen Recovery, and Ryegrass Production - Bilal Abdullah; Muhammad Bilal Khan Niazi; Zaib Jahan; Tariq Shah; Umer Shahzad Malik; Bilal Beig; Abid Mahmood; Ghulam Abbas Shah; Zahid Iqbal (Journal of Soil Science and Plant Nutrition, 2024)

Physiological and biochemical effects of biochar nanoparticles on spinach exposed to salinity and drought stresses - Aimun Rasheed; Sumera Anwar; Fahad Shafiq; Zaib-un-Nisa; Shahbaz Khan; Muhammad Ashraf (Environmental Science and Pollution Research, 2024)

Development and testing of environment friendly nanohybrid coatings for sustainable agriculture technologies - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Munir Zia; Ghulam Abbas Shah; Ayman A. Ghfar; Zahid Iqbal (Environmental Research, 2024)

Comparative genomics of light harvesting chlorophyll (LHC) gene family and impact of chlorophyll-A contents under drought stress in Helianthus annuus - Parwsha Zaib; Hafiz Muhammad Ahmad; Safira Attacha; Mahmood-Ur Rahman; Muhammad Rizwan Shafiq; Kousar Parveen; Sajid Fiaz; Kotb A. Attia; Saira Ishaq; Shazia Arif; Asmaa M. Abushady; Muhammad Jawad Umer (Journal of Plant Physiology, 2023)

Graphene-grafted bimetallic MOF membranes for hazardous & toxic contaminants treatment - Ayesha Rehman; Zaib Jahan; Muhammad Bilal Khan Niazi; Tayyaba Noor; Farhan Javed; Sarah I. Othman; Mostafa R. Abukhadra; Alam Nawaz (Chemosphere, 2023)

Thermochemical conversion of agricultural waste to hydrogen, methane, and biofuels: A review - Ahmed Khan; Muhammad Bilal Khan Niazi; Reema Ansar; Zaib Jahan; Farhan Javaid; Rafiq Ahmad; Hirra Anjum; Muhammad Ibrahim; Awais Bokhari (Fuel, 2023)

Development of ZnO-GO-NiO membrane for removal of lead and cadmium heavy metal ions from wastewater - Arslan Maqbool; Ameen Shahid; Zaib Jahan; Muhammad Bilal Khan Niazi; Muhammad Ali Inam; Ahmed M. Tawfeek; Emadeldin M Kamel; Muhammad Saeed Akhtar (Chemosphere, 2023)

Effects of micro(nano)plastics on soil nutrient cycling: State of the knowledge - Muhammad Salam; Huaili Zheng; Yingying Liu; Aneeqa Zaib; Syed Aziz Ur Rehman; Nimra Riaz; Moataz Eliw; Faisal Hayat; Hong Li; Fayuan Wang (Journal of Environmental Management, 2023)

Experimental investigation of a solar PCM heat exchanger for indoor temperature stabilization - Aurang Zaib; Abdur Rehman Mazhar; Tariq Talha; Muhammad Inshal (Energy and Buildings, 2023)

Wood as a green and sustainable alternative for environmentally friendly & flexible electronic devices - Hizbullah Malik; Muhammad Bilal Khan Niazi; Waheed Miran; Ahmed M. Tawfeek; Zaib Jahan; Emadeldin M. Kamel; Nouman Ahmed; Muhammad Saeed Akhtar (Chemosphere, 2023)

Fabrication and Evaluation of Anticancer Potential of Eugenol Incorporated Chitosan-Silver Nanocomposites: In Vitro, In Vivo, and In Silico Studies - Hamid Saeed Shah; Sumera Zaib; Muhammad Sarfraz; A. Alhadhrami; Mohamed M. Ibrahim; Aamir Mushtaq; Faisal Usman; Memoona Ishtiaq; Muhammad Sajjad; Hafiz Muhammad Mazhar Asjad; Umar Farooq Gohar (AAPS PharmSciTech, 2023)

Health risk assessment and bioaccumulation of potentially toxic metals from water, soil, and forages near coal mines of district Chakwal, Punjab, Pakistan - Nida Zainab; Shehzad Mehmood; Amna Shafiq-ur-Rehman; Adeela Munir; Zafar Iqbal Tanveer; Zaib Un Nisa; Muhammad Imran; Muhammad Tariq Javed; Hassan Javed Chaudhary (Environmental Geochemistry and Health, 2023)

Public debt and environment degradation in OIC countries: the moderating role of institutional quality - Fatima Farooq; Aurang Zaib; Muhammad Faheem; Muhammad Ali Gardezi (Environmental Science and Pollution Research, 2023)

Analyzing the impact of drought on agriculture: evidence from Pakistan using standardized precipitation evapotranspiration index - Anwar Hussain; Khan Zaib Jadoon; Khalil Ur Rahman; Songhao Shang; Muhammad Shahid; Nuaman Ejaz; Himayatullah Khan (Natural Hazards, 2023)

Influence of temperature on the development and reproduction of Spodoptera litura (Fabricius) on castor bean: implications for its use as a trap crop - Muhammad Zakria; Muhammad Shah Zaib; Khalid Abbas; Muhammad Sarmad; Syed Muhammad Zaka; Muhammad Noor-ul-Ane (Arthropod-Plant Interactions, 2022)

Nanotechnology-based controlled release of sustainable fertilizers. A review - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Umer Shahzad Malik; Mohammad Daud Khan; Juliana Heloisa Pinê Américo-Pinheiro; Dai-Viet N. Vo (Environmental Chemistry Letters, 2022)
The rising population is increasing food demand, yet actual crop production is limited by the poor efficiency of classical fertilizers. In particular, only about 40–60% of fertilizer nitrogen, 15–20% of phosphorus and 50–60% of potassium are used by crop plants, the rest ending polluting the environment. Nanofertilizers are promising alternatives. Here, we review plant nutrients, synthesis of zinc oxide nanoparticles, encapsulation of nanoparticles in fertilizers, and effect on plants.

Nano-structured dynamic Schiff base cues as robust self-healing polymers for biomedical and tissue engineering applications: a review - Umer Shahzad Malik; Muhammad Bilal Khan Niazi; Zaib Jahan; Mazhar Iqbal Zafar; Dai-Viet N. Vo; Farooq Sher (Environmental Chemistry Letters, 2022)
Polymer materials are vulnerable to damages, failures, and degradations, making them economically unreliable. Self-healing polymers, on the other hand, are multifunctional materials with superior properties of autonomic recovery from physical damages. These materials are suitable for biomedical and tissue engineering in terms of cost and durability. Schiff base linkages-based polymer materials are one of the robust techniques owing to their simple self-healing mechanism. These are dynamic reversible covalent bonds, easy to fabricate at mild conditions, and can self-reintegrate after network disruption at physiological conditions making them distinguished. Here we review self-healing polymer materials based on Schiff base bonds. We discuss the Schiff base bond formation between polymeric networks, which explains the self-healing phenomenon. These bonds have induced 100% recovery in optimal cases.

Designing Fusion Molecules from Antigens of Mycobacterium tuberculosis to Enhance Serodiagnostic Sensitivity in Latent TB Infection and Active TB State - Chandni Yaqoob; Saher Shahid; Aasia Khaliq; Zaib un Nisa; Imran H. Khan; Muhammad Waheed Akhtar (International Journal of Peptide Research and Therapeutics, 2022)

Potential perspectives of biodegradable plastics for food packaging application-review of properties and recent developments - Muhammad Imran Din; Tayabba Ghaffar; Jawayria Najeeb; Zaib Hussain; Rida Khalid; Hafsa Zahid (Food Additives & Contaminants: Part A, 2020)

Metal-induced nephrotoxicity to diabetic and non-diabetic Wistar rats - Muhammad Ahsan Riaz; Zaib Un Nisa; Azra Mehmood; Muhammad Sohail Anjum; Khurram Shahzad (Environmental Science and Pollution Research, 2019)

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability - Regie Lyn P. Santos-Cortez; Valeed Khan; Falak Sher Khan; Zaib-un-Nisa Mughal; Imen Chakchouk; Kwanghyuk Lee; Memoona Rasheed; Rifat Hamza; Anushree Acharya; Ehsan Ullah; Muhammad Arif Nadeem Saqib; Izoduwa Abbe; et al. (Human Genetics, 2018)

Seismic stratigraphy of the Mianwali and Bannu depressions, north-western Indus foreland basin - Asam Farid; Perveiz Khalid; Muhammad Y. Ali; Muhammad Asim Iqbal; Khan Zaib Jadoon (International Journal of Earth Sciences, 2018)

An application of variogram modelling for electrical resistivity soundings to characterize depositional system and hydrogeology of Bannu Basin, Pakistan - Asam Farid; Perveiz Khalid; Khan Zaib Jadoon; Muhammad Asim Iqbal; James Small (Geosciences Journal, 2017)

Alleviating the environmental heat burden on laying hens by feeding on diets enriched with certain antioxidants (vitamin E and selenium) individually or combined - Mohamed E. Abd El-Hack; Khalid Mahrose; Muhammad Arif; Maria Tabassum Chaudhry; Islam M. Saadeldin; Muhammad Saeed; Rab Nawaz Soomro; Imtiaz Hussain Raja Abbasi; Zaib Ur Rehman (Environmental Science and Pollution Research, 2017)

Applications of variogram modeling to electrical resistivity data for the occurrence and distribution of saline groundwater in Domail Plain, northwestern Himalayan fold and thrust belt, Pakistan - Asam Farid; Perviez Khalid; Klian Zaib Jadoon; Muhammad Asim Iqbal; Muhammad Shafique (Journal of Mountain Science, 2017)

Empirical evidence of cold stress induced cell mediated and humoral immune response in common myna (Sturnus tristis) - Mansur A. Sandhu; Anila Zaib; Muhammad S. Anjum; Mazhar Qayyum (International Journal of Biometeorology, 2015)

Synthesis, characterization and urease inhibition, in vitro anticancer and antileishmanial studies of Ni(II) complexes with N,N,N′-trisubstituted thioureas - Muhammad Khawar Rauf; Samad Yaseen; Amin Badshah; Sumera Zaib; Raffia Arshad; Imtiaz-ud-Din; Muhammad Nawaz Tahir; Jamshed Iqbal (JBIC Journal of Biological Inorganic Chemistry, 2015)